Assessing inflammatory protein factors in inflammatory bowel Disease using multivariable mendelian randomization - Qiang Su; Yun Lu; Song He; Jiang Liang; Song Huang; Yuanli He; Zhenxiang An (Scientific Reports)
Abstract Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), decreases quality of life and causes disability. The underlying processes are not fully understood. This study uses Mendelian randomization (MR) analysis to identify cytokines that may be associated with UC and CD, aiding in early diagnosis and treatment decisions. Methods Genome-wide association study (GWAS) data for inflammatory cytokine levels were obtained from a cohort of 14,824 individuals of European descent. The outcome data were then analyzed using summary-level GWAS data for UC and CD from the International Inflammatory Bowel Disease Genetics Consortium (IIBDGC). The analysis was primarily conducted using inverse-variance weighted (IVW) methods, with MR-Egger and weighted median serving as supplementary analyses. Sensitivity analyses included Cochran’s Q test, MR-Egger intercept test, MR-PRESSO, and leave-one-out analysis.The inflammatory cytokines were subjected to additional scrutiny through the application of the Steiger test and reverse Mendelian randomization analysis. Subsequently, multivariable Mendelian randomization (MVMR) was employed to examine the associations of metabolites on UC and CD, in conjunction with linkage disequilibrium score regression (LDSC) and colocalization analysis. After FDR correction, we identified significant genetic associations of two inflammatory proteins (CXCL5 and CXCL9) with UC, and CXCL5 and IL-18R1 with CD. These findings were further validated by MVMR. Colocalization analyses demonstrated substantial genetic overlap between inflammatory proteins and IBD, with CXCL5 showing strong evidence of shared genetic variants with UC, and CXCL9 exhibiting genetic colocalization with CD, suggesting common genetic determinants underlying these inflammatory protein-IBD relationships. The current work presents evidence that presents evidence of significant associations between seven inflammatory protein factors and UC, as well as three inflammatory protein factors and CD. These findings provide novel insights into the biological mechanisms of IBD, and have implications for the screening, prevention, and treatment of IBD.